Instruction: Teaching or Marketing? - Susan B. Ardis (Issues in Science and Technology Librarianship)
Presents views on library instruction. Scope of teaching; Comparison between the goals of marketing and library instruction; Reason information literacy instruction is considered a form of marketing.